1992
DOI: 10.1007/bf00018454
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a rice ?-glucanase gene regulated by ethylene, cytokinin, wounding, salicylic acid and fungal elicitors

Abstract: A rice beta-glucanase gene was sequenced and its expression analyzed at the level of mRNA accumulation. This gene (Gns1) is expressed at relatively low levels in germinating seeds, shoots, leaves, panicles and callus, but it is expressed at higher levels in roots. Expression in the roots appears to be constitutive. Shoots express Gns1 at much higher levels when treated with ethylene, cytokinin, salicylic acid, and fungal elicitors derived from the pathogen Sclerotium oryzae or from the non-pathogen Saccharomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
1
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 55 publications
5
52
1
1
Order By: Relevance
“…Increases in both chitinase and glucanase activities were detected only in P. syringae-inoculated leaves and not systemically. However, the transcription of a chitinase (Nishizawa and Hibi, 1991) and a glucanase (Simmons et al, 1992) was induced in rice by pathogen-derived elicitors and SA. Additionally, application of 2,6-dichloro-isonicotinic acid, a possible SA analog that activates natural plant defenses, induced resistance in rice to M .…”
mentioning
confidence: 99%
“…Increases in both chitinase and glucanase activities were detected only in P. syringae-inoculated leaves and not systemically. However, the transcription of a chitinase (Nishizawa and Hibi, 1991) and a glucanase (Simmons et al, 1992) was induced in rice by pathogen-derived elicitors and SA. Additionally, application of 2,6-dichloro-isonicotinic acid, a possible SA analog that activates natural plant defenses, induced resistance in rice to M .…”
mentioning
confidence: 99%
“…Phytohormones are also thought to be indispensable in signaling pathways that involve perception and transduction of external signals (Klee and Estelle, 1991). Cytokinins have attracted particular interest because of their diverse physiological functions in response to light (Miller, 1956;Su and Howell, 1995;von Arnim and Deng, 1996), nutrients (Yu et al, 1998), growth (Chaudhury et al, 1993;Brzobohaty et al, 1994), and even wounding (Simmons et al, 1992). Recent work has revealed that cytokinins enhance the transcription of several genes involved in nutrient metabolism (Lu et al, 1990;Dominov et al, 1992;Andersen et al, 1996;Ehnes and Roitsch, 1997) and self-defense (Simmons et al, 1992;Sano et al, , 1996.…”
mentioning
confidence: 99%
“…A decrease in the hemicellulose content in rice culms may result from a higher rate of β-glucan degradation, from a lower rate of β-glucan synthesis, or both. Previously, we found that the Gns1 gene, a putative 1,3;1,4-β-glucanase gene of rice (Simmons et al, 1992), is highly expressed in ripening rice culms (Nemoto et al, 1999;Baba et al, 2001), which suggests that the higher rate of β-glucan degradation might be the main cause of the decrease in the hemicellulose content in ripening culms. The rate of β -glucan degradation might be very high in ripening culms, presumably because of its translocation to the panicle.…”
Section: Resultsmentioning
confidence: 97%